The expression and role of the Lem-D proteins Ankle2, Emerin, Lemd2, and TMPO in triple-negative breast cancer cell growth - Rose, Maddison; Burgess, Joshua T.; Cheong, Chee Man; Adams, Mark N.; Shahrouzi, Parastoo; O’Byrne, Kenneth J.; Richard, Derek J.; Bolderson, Emma (Frontiers in Oncology, 2024)
Background Triple negative breast cancer (TNBC) is a sub-classification of breast carcinomas which leads to poor survival outcomes for patients. TNBCs do not possess the hormone receptors that are frequently targeted as a therapeutic in other cancer subtypes and therefore, chemotherapy remains the standard treatment for TNBC. Nuclear envelope proteins are frequently dysregulated in cancer cells, supporting their potential as novel cancer therapy targets. The Lem (LAP2, Emerin, MAN1 domain, Lem-D) domain proteins are a family of inner nuclear membrane proteins, which share a ~45-residue Lem-domain. The Lem-D proteins, including Ankle2, Lemd2, TMPO and Emerin, have been shown to be associated with many of the hallmarks of cancer. This study aimed to define the association between the Lem-D proteins and TNBC and determine whether these proteins could be promising therapeutic targets. Methods GENT2, TCGA and KM plotter were utilised to investigate the expression and prognostic implications of several Lem-D proteins: Ankle2, TMPO, Emerin, and Lemd2 in publicly available breast cancer patient data. Immunoblotting and immunofluorescent analysis of immortalised non-cancerous breast cells and a panel of TNBC cells were utilised to establish whether protein expression of the Lem-D proteins was significantly altered in TNBC. SiRNA was used to decrease individual Lem-D protein expression and functional assays, including proliferation assays and apoptosis assays, were conducted. Results The Lem-D proteins were generally overexpressed in TNBC patient samples at the mRNA level and showed variable expression at the protein level in TNBC cell lysates. Similarly, protein levels were generally negatively correlated with patient survival outcomes. siRNA-mediated depletion of the individual Lem-D proteins in TNBC cells induced aberrant nuclear morphology, decreased proliferation, and induced cell death. However, minimal effects on nuclear morphology or cell viability were observed following Lem-D depletion in non-cancerous MCF10A cells. Conclusion There is evidence to suggest that Ankle2, TMPO, Emerin and Lemd2 expression are correlated with breast cancer patient outcomes, but larger patient sample numbers are required to confirm this. siRNA mediated depletion of these proteins was shown to specifically impair TNBC cell growth, suggesting that the Lem-D proteins may be a specific anti-cancer target.